PENGARUH LOKASI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA SHOWROOM SEPEDA MOTOR KEKANG DI NANGALIMANG MAUMERE - Maria Ancistra Dian Purnama Triani; Antonius Phillipus K.Gheta; Paulus Juru (Jurnal Projemen UNIPA, 2026)
This study aimed to examine the effect of location and promotion on consumer purchase decisions at the Kekang Motorcycle Showroom in Nangalimang, Maumere. The independent variables in this study were location (X1) and promotion (X2), while the dependent variable was the purchasing decision (Y). This study employed a quantitative research method. The sample consisted of 75 respondents, selected using an accidental sampling technique. Data were collected through observation, questionnaires, and documentation. The data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results indicated that location had a positive and significant effect on purchase decisions at the Kekang Motorcycle Showroom in Nangalimang, Maumere. Meanwhile, promotion did not have a significant effect on purchase decisions. Simultaneously, location and promotion had a significant effect on purchase decisions. Thus, consumer purchase decisions were more strongly influenced by location than by promotion. Keywords: Location, Promotion, Consumer Purchase Decision.